2020
DOI: 10.1084/jem.20201414
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 inhibition diminishes KRASG12C cycling and promotes tumor microenvironment remodeling

Abstract: KRAS is the most frequently mutated human oncogene, and KRAS inhibition has been a longtime goal. Recently, inhibitors were developed that bind KRASG12C-GDP and react with Cys-12 (G12C-Is). Using new affinity reagents to monitor KRASG12C activation and inhibitor engagement, we found that an SHP2 inhibitor (SHP2-I) increases KRAS-GDP occupancy, enhancing G12C-I efficacy. The SHP2-I abrogated RTK feedback signaling and adaptive resistance to G12C-Is in vitro, in xenografts, and in syngeneic KRASG12C-mutant pancr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(194 citation statements)
references
References 86 publications
13
163
0
Order By: Relevance
“…Indeed, recently updated phase 1 results confirm that sotorasib and adagrasib are well tolerated in patients, with 11.6% of patients receiving sotorasib experiencing grade 3/4 treatment-related adverse effects [ 35 ]. Several possible inhibitory partners have been identified, including SHP2, receptor tyrosine kinases, PI3K and PD-1/L1 [ 27 , 56 , 65 ]. However, there remains a lack of consensus on which of these targets should be prioritised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recently updated phase 1 results confirm that sotorasib and adagrasib are well tolerated in patients, with 11.6% of patients receiving sotorasib experiencing grade 3/4 treatment-related adverse effects [ 35 ]. Several possible inhibitory partners have been identified, including SHP2, receptor tyrosine kinases, PI3K and PD-1/L1 [ 27 , 56 , 65 ]. However, there remains a lack of consensus on which of these targets should be prioritised.…”
Section: Discussionmentioning
confidence: 99%
“…Either inhibitor alone had minimal effects on murine PDAC and NSCLC models, whereas G12C/SHP2 co-inhibition conferred extended survival in all models with no evidence of toxicity. SHP2 co-inhibition also appears to lead to a more favourable immune microenvironment, and sensitised tumours to PD-1 inhibition [ 65 ]. In agreement with these findings, the SHP2 inhibitor TNO155 has been shown to overcome feedback reactivation of RTK signalling induced by G12C inhibition and was found to act synergistically with the G12C inhibitor Cpd 12a to inhibit proliferation in KRAS G12C cell lines.…”
Section: Maximising the Potential Of G12c Inhibitorsmentioning
confidence: 99%
“…"Driver" mutations (e.g., amplified or mutant RTKs, mutant KRAS) significantly-and differentially-also have tumor cell-intrinsic andextrinsic effects and evoke distinct cellular and humoral responses in different tissues (3). Consequently, SHP2is have important, potentially driver-specific, effects on the tumor microenvironment (TME), including potentially complex effects on anti-tumor immunity (2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…As the response to targeted therapies in patients almost certainly reflects the composite of direct anti-tumor actions and effects on the TME, CDXs, PDXs, and SQ syngeneic models could provide incomplete or even misleading information about SHP2i action. For example, we found that SHP2i, alone or in combination with KRAS-G12C inhibitor (G12Ci), increased intratumor T cells in KRAS G12C -driven non-small cell lung cancer (NSCLC) and pancreas ductal adenocarcinoma (PDAC) (4). However, the degree of T cell function is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation